Overview of Nepalese Politics from a Managerialism Perspective - Katuwal, Chandan (Sahayaatra सहयात्रा, 2023)
This study examines how managerial practices affect political decision-making and policy execution in Nepal from a managerial perspective. The research aims at the main characteristics of Nepal's political system and how effectively management strategies work to encourage good governance. The study argues that in order to foster effective leadership, boost accountability, and shape the country's future, Nepali political leaders can gain from using managerial principles including servant leadership, effective delegation, teamwork, openness, communication, and transparency. Through a literature analysis, the study identifies and evaluates significant programs and strategies employed to solve political concerns in Nepal. The study employs a qualitative research design that includes a thorough examination of secondary sources such as academic articles, government reports, international agencies and NGO reports. This article explores management strategies that support effective governance in Nepal. It looks at how managerial practices influence political judgments and the implementation of policies The researcher further recommends continuing to implement managerialism tactics like PBB and PPPs and accommodating practices like RBM & e-governance to boost managerialism in the political system. One of the study's drawbacks is its limited focus on management viewpoints.